2014
DOI: 10.1038/eye.2014.148
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic membrane transplantation in surgical management of ocular surface squamous neoplasias: long-term results

Abstract: Objective To evaluate the long-term efficacy of amniotic membrane transplantation for ocular surface reconstruction in the surgical management of ocular surface squamous neoplasia (OSSN). Methods OSSN in 21 patients (7 female, 14 male patients) was managed with excisional biopsy, cryotherapy, corneal epitheliectomy with absolute alcohol application when the cornea is involved, lamellar sclerectomy and adjunctional absolute alcohol application to the base when episclera is involved, and ocular surface reconstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 23 publications
2
31
0
1
Order By: Relevance
“…However, for large and diffuse lesions without clear margins, even intended excisional biopsy may not remove the entire lesion. Also, for large or recurrent lesions, excisional biopsies lead to increased risks of limbal stem cell deficiency, symblepharon, and scarring 10,11 . Lastly, as medical options for treatment of OSSN increase in number and become more utilized, non-invasive methods of diagnosis become more important 12 .…”
Section: Ocular Surface Squamous Neoplasiamentioning
confidence: 99%
“…However, for large and diffuse lesions without clear margins, even intended excisional biopsy may not remove the entire lesion. Also, for large or recurrent lesions, excisional biopsies lead to increased risks of limbal stem cell deficiency, symblepharon, and scarring 10,11 . Lastly, as medical options for treatment of OSSN increase in number and become more utilized, non-invasive methods of diagnosis become more important 12 .…”
Section: Ocular Surface Squamous Neoplasiamentioning
confidence: 99%
“…3,12,14 Cryopreserved AM is the most commonly used form because it preserves the intact basement membrane and contains a higher amount of soluble, wound-healing modulating factors. 7,15,16 Studies show that it facilitated complete epithelial healing, with good or excellent cosmesis, in patients with ocular surface neoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The AM promotes epithelialization; inhibits fibrosis; has antiscarring, antiangiogenic, and antiinflammatory properties; and has a high hydraulic conductivity. [3][4][5][6] It has been used in ophthalmology for corneal disorders and conjunctival reconstructions after the excision of pterygium, tumors, and symblepharon lysis. [4][5][6][7][8][9] AM is commercially available in airdried or cryopreserved forms.…”
mentioning
confidence: 99%
“…Amniotic membrane has been used for various other conjunctival defects and abnormalities. Palamar et al 41 recently reported on their experience using amniotic membrane for ocular surface reconstruction following the excision of ocular surface squamous neoplasia and found it to be effective for large conjunctival defects. Yang et al 42 recently reported that patients with severe chronic atopic keratoconjunctivitis could benefit from surgical management using amniotic membrane.…”
Section: Pterygium and Conjunctival Reconstructionmentioning
confidence: 99%